2011
DOI: 10.1590/s0102-311x2011000900017
|View full text |Cite
|
Sign up to set email alerts
|

Recursos y capacidades de servicios de emergencia para atención de lesiones por traumas en Perú

Abstract: Los objetivos de este trabajo fueron determinar la percepción de los recursos y capacidades de los servicios de emergencia en tres ciudades del Perú, utilizando las guías publicadas por la Organización Mundial de la Salud: Guidelines for Essential Trauma Care. Estudio transversal, realizado en 8 establecimientos de salud públicos y privados, en las ciudades de Lima, Ayacucho y Pucallpa. Se aplicaron cuestionarios semi-estructurados a los responsables de los servicios calificando, de acuerdo a su percepción, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…There are also, however, victim, vehicle, and environmental factors that, together with opportunity and quality of care, can influence the fatality rate. These factors are difficult to document and measure, and for example, adequate human resources [51] and insurance coverage for RTIs [52]remain a challenge to be addressed in the Peruvian setting.…”
Section: Discussionmentioning
confidence: 99%
“…There are also, however, victim, vehicle, and environmental factors that, together with opportunity and quality of care, can influence the fatality rate. These factors are difficult to document and measure, and for example, adequate human resources [51] and insurance coverage for RTIs [52]remain a challenge to be addressed in the Peruvian setting.…”
Section: Discussionmentioning
confidence: 99%
“…One method to improve the quality of hospital care that has demonstrated cost-effectiveness is the implementation of improvement programs for trauma and emergency services laid out in the Guidelines for Essential Trauma Care, published by the WHO 4 . Their application to our health system has been insufficient at present 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work was limited to one study of emergency services in an urban area in El Salvador 10 and other studies in South America with limited scopes of assessment such as trauma or surgery. [11][12][13][14][15] In our study we found some areas of adequate capacity including in supplies such as PPE and staffing infrastructure. However, there were also major deficiencies including a severe shortage of critical medications in clinics, and a widespread shortage of pediatric equipment.…”
Section: Discussionmentioning
confidence: 54%
“…There are few organized prehospital services and most people have to rely on public or self-transport to access emergency care. 9 Although previous work has evaluated hospitals in urban areas, 10 and focused studies on limited scopes of service such as trauma or surgery have been done, [11][12][13][14][15] the ability to provide a standardized set of emergency services, or "emergency services capacity" in rural areas of Central and South America has not been systematically studied.…”
Section: How Does This Improve Population Health?mentioning
confidence: 99%